Ethnophysics in the Structure of Baileo Traditional Houses as a Source of Elementary School Science Learning - Sriwahyuni, Eka; Siregar, Hiba Dertyana; Sofyan, Abdul (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2025)
Baileo traditional house is a distinctive cultural heritage of Maluku containing physics principles for elementary science learning. Ethnophysics learning integrates local cultural values in natural science teaching. This research aims to identify physics concepts in Baileo traditional house structure and analyze their integration into elementary science learning. The research method used qualitative approach through literature study by analyzing 35 relevant articles. Results show that Baileo traditional house structure contains physics concepts including object equilibrium, moment of force, heat transfer, conduction, thermal insulation, light, air flow, pressure, and fluid suitable for elementary science materials. Baileo traditional house can serve as science learning object connecting physics concepts with local culture, aligned with Science Learning Outcomes phases A and B of Merdeka Curriculum emphasizing observation of natural phenomena and surrounding environment. Through Baileo house as study object, students learn physics concepts concretely and meaningfully through local culture, while developing Pancasila Student Profile such as collaboration, local wisdom, and critical thinking. This aligns with Merdeka Curriculum principles encouraging integration between science and students’ real-life contexts through local culture.